PENGARUH PEMBELAJARAN DARING MATA KULIAH MANDARIN KOMPREH ENSIF TERHADAP KEEFEKTIFAN PEMBELAJARAN MAHASISWA PRODI PBM - Rusmita, Devi; Thamrin, Lily; Suhardi, Suhardi (Universitas Tanjungpura, 2023)
This research aims to determine how effective the implementation of online learning is for students. The impact of Covid-19 has led to the implementation of online learning. Online learning has many challenges, including student